Expression of schizophrenia biomarkers in extraocular muscles from patients with strabismus: an explanation for the link between exotropia and schizophrenia? - Agarwal,Andrea B.; Christensen,Austin J.; Feng,Cheng-Yuan; Wen,Dan; Johnson,L. Alan; von Bartheld,Christopher S. (PeerJ, 2017)
Recent studies have implicated exotropia as a risk factor for schizophrenia. We determined whether schizophrenia biomarkers have abnormal levels of expression in extraocular muscles from patients with strabismus and explored whether differences in gene expression between medial and lateral rectus muscles may explain the specific association of schizophrenia with exotropia but not esotropia. Samples from horizontal extraocular muscles were obtained during strabismus surgery and compared with age- and muscle type-matched normal muscles from organ donors. We used PCR arrays to identify differences in gene expression among 417 signaling molecules. We then focused on established schizophrenia-related growth factors, cytokines, and regulators of the extracellular matrix. Among 36 genes with significantly altered gene expression in dysfunctional horizontal rectus muscles, over one third were schizophrenia-related: CTGF, CXCR4, IL1B, IL10RA, MIF, MMP2, NPY1R, NRG1, NTRK2, SERPINA3, TIMP1, TIMP2, and TNF (adjusted p value ≤ 0.016667). By PCR array, expression of three of these genes was significantly different in medial rectus muscles, while eleven were significantly altered in lateral rectus muscles. Comparing baseline levels between muscle types, three schizophrenia-related genes (NPY1R, NTRK2, TIMP2) had lower levels of expression in medial rectus muscles. Despite the surprisingly large number of schizophrenia-related genes with altered gene expression levels in dysfunctional muscles, the lack of specificity for medial rectus muscles undermines a model of shared, region-specific gene expression abnormalities between exotropia and schizophrenia, but rather suggests consideration of the alternative model: that exotropia-induced aberrant early visual experiences may enable and/or contribute as a causative factor to the development of schizophrenia.
Keywords: Strabismus; Gene expression; PCR Array; Growth factor; Extraocular muscle; Biomarker; Extracellular matrix; Schizophrenia